Discontinuous continuity: Structural change and its (divergent) meanings in Latin American structuralism and neo-structuralism - Ormaechea, Emilia Laura (2020)
This paper analyses the continuities and discontinuities regarding the concept of structural change in Latin American structuralism and neo-structuralism and considers the global context in which these ideas and their variations are produced. In this sense, the transformations of capitalism from 1950 onwards are taken into account as are the diagnoses and strategies promoted by the ECLAC to ultimately achieve structural change through structuralism and neo-structuralism. How the role of the state is conceived in each of these contexts and the consequences derived from state intervention to promote the structural change are also analysed.